Analisis Perbandingan Prestasi Belajar Mata Kuliah Ilmu Gizi Mahasiswa Kesehatan Berdasarkan Jalur Penerimaan Mahasiswa Baru - Elita Mawarni (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2019)
This descriptive study examined (1) to obtained description learning achievement of students received through PMDK and Reguler pathways on Diploma of Nursing and Diploma of Midewifery for Nutrition of Sciences's subject at STIKES Banyuwangi; (2) to determine the differences between learning achievement of students received through PMDK and Reguler pathways on Diploma of Nursing and Diploma of Midewifery at STIKES Banyuwangi. A documentation technique of 82 students was recruited from diploma of nursing and diploma of midwifery with year entry on 2015 at STIKES Banyuwangi. Descriptive statistics and inferential statistics were utilized to analyse the data. Result of research analysis showed that the learning achievement of Diploma Nursing and Midewifery Department’s Students of STIKES Banyuwangi received in year 2015 through PMDK were averagely of 3,00 and dominated by students who have learning achievement with satisfactory category; learning achievement of Diploma Nursing and Midewifery Department’s students of STIKES Banyuwangi received through Reguler pathways were averagely 2.89 and dominated by students who have learning achievement with satisfactory categories. The study found that learning achievement throught PMDK Diploma of Nursing and diploma of Midewifery averagely of 3,00 and dominated by satisfactory category; while learning achievement by reguler averagely 2.89 and dominated by satisfactory category; based on the testing of hypothesis, this study there were not differences between learning achievement of students received through PMDK and Reguler pathways on Diploma of Nursing and Diploma of Midewifery for Nutrition of Sciences's subject at STIKES Banyuwangi.